Hitherto unknown sexual morphs of Brachysiphoniella montana (van der Goot, 1917) (Hemiptera: Aphididae) - Kanturski, Mariusz; Lee, Yerim (Zootaxa, 2022)
Here, we describe the hitherto unknown sexual morphs (oviparous females and males) of Brachysiphoniella montana (van der Goot, 1917) (Aphididae: Aphidinae: Macrosiphini). Oviparous females and males from the Republic of Korea are described and illustrated in details. Descriptions of sexual morphs of this species confirm the holocyclic life cycle of Brachysiphoniella in areas with cooler months. Notes about distribution and host plants of the species are also given.